2020
DOI: 10.1093/jtm/taaa176
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of travel restrictions for COVID-19 control in Latin America through network connectedness

Abstract: We analyze the COVID-19 pandemic development in Latin America by network analysis to demonstrate the effectiveness of air travel restriction in reducing pandemic risk and provide risk analysis for air travel reopening in Latin America. We reinforce the importance of restricting air travel before and during local transmission of COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 2 publications
1
26
0
Order By: Relevance
“…Spatial-temporal maps of Europe at 14-day intervals between May and June 2020 were generated. As countries serving as air transportation hubs were particularly prone to the spread of COVID-19 [16], spatial-temporal maps at the country level for these hubs have been plotted to investigate network connectedness between the countries harboring these hubs during the growth of the pandemic. Each bubble represents a country with airports defined as among the top 10 air transportation hubs in Europe by the Official Airline Guide MegaHub Index of 2019 [25].…”
Section: Data Visualizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Spatial-temporal maps of Europe at 14-day intervals between May and June 2020 were generated. As countries serving as air transportation hubs were particularly prone to the spread of COVID-19 [16], spatial-temporal maps at the country level for these hubs have been plotted to investigate network connectedness between the countries harboring these hubs during the growth of the pandemic. Each bubble represents a country with airports defined as among the top 10 air transportation hubs in Europe by the Official Airline Guide MegaHub Index of 2019 [25].…”
Section: Data Visualizationmentioning
confidence: 99%
“…A study on COVID-19 control in Latin America suggested that countries serving as air transportation hubs are more prone to disease transmission. The practicable use of travel data for the prediction of the risk of the COVID-19 pandemic has been previously reported [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of these studies have shown that lockdown measures, in particular, appear to be one of the most effective approaches to limiting the spread of infections [ 15 ]. Studies have also shown that the imposition of travel restrictions has been effective in reducing correlations in the numbers of infected people across different countries [ 16 , 17 ]. In this paper, we develop a dynamic pandemic network model to evaluate the performances of several major policies in terms of controlling the spread of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Travel restriction measures have varied from country to country and cases of imported lineages have been confirmed since the early phase of COVID-19 pandemic. 5 , 6 Despite SARS-CoV-2 genetic diversity across states seems to be geographically compartmentalized, 7 the relaxing distancing control measures and the increasing intercity population mobility have contributed to the spread of multiple lineages across different geographical regions in the country.…”
mentioning
confidence: 99%